Analisis Sustainable Competitive Advantage Apotek K24 cabang Demangan, Yogyakarta - , Fia Trisfikasari Nurjaman; , Drs. Wakhid Slamet Ciptono, M.B.A., M.P.M., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this research is to analyze the sustainable competitive advantage of K24 Apothecary Demangan Branch, Yogyakarta. K24 Apothecary is one of the biggest chains of 24-hours operating apothecaries in Indonesia, and the first ones using franchise system. The research is conducted on the Demangan Branch of K24 Apothecary, one of the biggest branch apothecary, which the assumption that it will portray the condition of K24 Apothecaries in general. The strategies that are employed by K24 Apothecaries are innovation and differentiation strategies. K24 Apothecaris are expected to be able to sustain their companyâs competitive advantage ahead to their competition and to keep becoming the market leader of Indonesiaâs apothecary chains. A company can be labelled reaching sustainable competitive advantage if a number of buyer prefer to use the products or services offered by the company over the competitors, and that preference is going for some time. The analysis used to determine whether K24 Apothecary Demangan Branch Yogyakarta achieved sustainable competitive advantage were Importance Performance Analysis (IPA) which conveys the five dimensions of Service Quality which are Reliability, Responsiveness, Assurance, Empathy, and Tangible. Many literatures stated that IPA has been widely used in many field (of science), such as Marketing Strategy, Operational Strategy, Human Resource Evaluation, and better Company Resource Allocation. This method has been introduced as a framework for understanding customer satisfaction as a function of attribute importance expectancy and evaluation of performance. The results of strategic analysis of Importance Performance Analysis indicate that K24 Apothecary has been succesful in implementing a differentiation strategy. Guarantee of complete availability of medicine, price which is appropriate to the quality of medicine, and premium service is located in the B quadrant is indeed the companyâs competitive advantage. Eventhough for now there are many competitor chains such as Apotex and Kimia Farma which also operates 24-hours,as the first chains of 24-hours operating apothecaries, K24 apothecaries has firmly creating strong preference in the consumersâ mind.